The Influence of Employer Branding, Work Motivation, and Career Development on Employee Retention in Hotels and Lodgings in Tourist Areas Cipanas Garut - Supardi Yapan (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Background behind study This is based on the high employee turnover rate in the hospitality industry, which has the potential to reduce service quality and increase HR management costs. This aim analyze the influence of employer branding, motivation work and development career to retention employees at hotels and inns in the area tour Cipanas Garut.Research use mixed methods approach with causal associative design and explanatory survey method combined with qualitative analysis.The results of the quantitative analysis simulation show that employer branding has a positive and significant effect on employee retention; the more positive the organization's image as an attractive and proud workplace, the higher the employee's tendency to stay. Work motivation also has a positive and significant effect on employee retention, indicating that the fulfillment of work needs and organizational support strengthen employees' commitment to stay. Career development has been shown to have a positive and significant effect on employee retention; a clear career path and the availability of development opportunities increase employees' desire to stay long-term. In a way Simultaneously, employer branding, work motivation, and career development significantly influence employee retention, with employer branding as the most dominant variable. Qualitative analysis supports this finding, where themes of brand pride (employer branding), superior support (motivation), and clarity of career prospects (career development) emerged as reasons for employee retention. main employee endure.